The imagination machine : how to spark new ideas and create your company's future - Reeves, Martin, (Harvard Business Review Press, 2021)
"A guide for mining the imagination to find powerful new ways to succeed We need imagination now more than ever-to find opportunities in adversity, rethink our businesses, and discover new paths to growth. Yet too many companies have lost their ability to imagine. What is this mysterious capacity? How does imagination work? And how can organizations keep it alive and harness it systematically? The Imagination Machine answers these questions and more. Drawing on the experience and insights of CEOs across several industries, as well as lessons from neuroscience, computer science, psychology, and philosophy, BCG's Martin Reeves and Jack Fuller provide a fascinating look into the mechanics of imagination and lay out a six-step process for creating ideas and bringing them to life. These steps are: Trigger: disrupt existing mental models and put ourselves in a more imaginative mindset, rethink: focus on "what could be" rather than "what is", act: create a feedback loop from the mind to the world and back again, amplify: spread an evolving idea to others to create collective imagination, codify: imagine a new organizational "machine" that will capture and exploit a new idea while leaving room for future reimagination, sustain: keep imagination alive to run and reinvent your company at the same time. Imagination is one of the least understood but most crucial ingredients of business success. It's what makes the difference between an incremental change and the kinds of pivots and paradigm shifts that are essential to success-especially during a crisis. The Imagination Machine is the guide you need to demystify and operationalize this powerful human capacity, to inject new life into your company, and to head into unknown territory with the right tools by your side"--